Isolation and Molecular Characterization of Chitinase-Deficient Bacillus licheniformis Strains Capable of Deproteinization of Shrimp Shell Waste To Obtain Highly Viscous Chitin - Waldeck, Jens; Daum, Gabriele; Bisping, Bernward; Meinhardt, Friedhelm (Applied and Environmental Microbiology, 2006)
Proteolytic but chitinase-deficient microbial cultures were isolated from shrimp shell waste and characterized. The most efficient isolate was found to be a mixed culture consisting of two Bacillus licheniformis strains, which were first determined microscopically and physiologically. Molecular characterization was carried out by sequencing the 16S rRNA gene of both strains. According to the residual protein and ash content, the chitin obtained by fermentation of such a mixed culture was found to be comparable to a commercially available, chemically processed product. However, the strikingly high viscosity (80 versus 10 mPa of the commercially available sample) indicates its superior quality. The two strains differed in colony morphology and in their secretion capabilities for degradative extracellular enzymes. Sequencing of the loci encoding amylase, cellulase, chitinases, and proteases, as well as the degS/degU operon, which is instrumental in the regulation of degradative enzymes, and the pga operon, which is responsible for polyglutamic acid production, revealed no differences. However, a frameshift mutation in chiA, encoding a chitinase, was validated for both strains, providing an explanation for the ascertained absence of chitinolytic activities and the concomitant possibility of producing highly viscous chitin in a fermentational deproteinization process.